Cognitive Skills within the Inner Development Goals (IDG) Framework: Empowering Sustainable Careers and Sustainable Development - Shtaltovna, Yuliya; Rodriguez Carreon, Vivianna; Lindencrona, Fredrik; Donald, William E. (GILE Journal of Skills Development, 2024)
Our theoretical manuscript aims to explore the role that dimension two, ‘Thinking-Cognitive Skills’ of the Inner Development Goals (IDG) framework, can play in empowering sustainable careers and sustainable development. We begin by setting the scene before introducing the theoretical framework, which combines the IDG framework and Sustainable Career Ecosystems Theory (SCET). Our attention then turns to systematically considering each of the components of dimension two of the IDG framework. These include (a) critical thinking, (b) complexity awareness, (c) perspective skills, (d) sense-making, and (e) long-term orientation and visioning. The theoretical contribution comes from integrating the IDG framework and SCET. Practical implications come from offering eight pragmatic recommendations to empower students in the context of higher education to prepare for sustainable careers and sustainable development: (i) curriculum design, (ii) interdisciplinary approach, (iii) experiential learning, (iv) faculty development, (v) assessment and evaluation, (vi) campus culture, (vii) collaboration and external partners, and (viii) research and innovation. Limitations and a future research agenda are also provided.